2017
DOI: 10.1620/tjem.243.1
|View full text |Cite
|
Sign up to set email alerts
|

Nation-Wide Implementation of Disaster Medical Coordinators in Japan

Abstract: In the 2011 Great East Japan Earthquake (GEJE), successful medical and public health coordination by pre-assigned disaster medical coordinators saved many affected people, though the coordination itself had difficulties. This study aims to clarify the implementation and the challenges of disaster medical coordinators in Japan. We performed questionnaire surveillance in 2012 and 2014 to all prefectural government on assignment of disaster medical coordinators, their expected roles and supporting system. Out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Accordingly, the main responsibility of the HQ-D-PHC in Atami city was providing appropriate living support for the evacuated refugees, rather than urgent medical intervention. After the experience of Great East Japan Earthquake, to prevent disaster-related deaths among refugees over the long term, the Ministry of Health, Labour and Welfare decided to develop DMAT members as disaster medical coordinators for coordination among various medical organizations under the leadership of PHCs 4) . Human resources trained based on this framework have already contributed to disaster management following the Kumamoto Earthquake in 2016, and contributed to disaster management following the Atami debris flow in 2021 5) .…”
Section: .Discussionmentioning
confidence: 99%
“…Accordingly, the main responsibility of the HQ-D-PHC in Atami city was providing appropriate living support for the evacuated refugees, rather than urgent medical intervention. After the experience of Great East Japan Earthquake, to prevent disaster-related deaths among refugees over the long term, the Ministry of Health, Labour and Welfare decided to develop DMAT members as disaster medical coordinators for coordination among various medical organizations under the leadership of PHCs 4) . Human resources trained based on this framework have already contributed to disaster management following the Kumamoto Earthquake in 2016, and contributed to disaster management following the Atami debris flow in 2021 5) .…”
Section: .Discussionmentioning
confidence: 99%
“…Countries with more advanced disaster preparedness and response programs, such as the United States and Japan, have experienced catastrophic disasters in the past and have improved through these experiences. [8][9][10][11][12] A thorough review and analysis of the process of coping with previous disasters could lead to a well-planned disaster preparedness system in South Korea. Previous studies of development of standardized core competencies for disaster medicine and public health revealed that these competencies were determined through an objective, specific, and scientific process.…”
Section: Discussionmentioning
confidence: 99%
“…Lower number of meeting participants was associated with anxiety reduction and higher subjective comprehension. Egawa et al (2017b) described the nation-wide implementation of disaster medical coordinators in more than 80% of prefectures in Japan. The fist disaster medical coordinator was assigned in Hyogo Prefecture soon after the 1995 GHAE, but was only followed by four prefectures including Miyagi, until the GEJE reminded its necessity.…”
Section: Articles Related With Geje In Tjem After 2011mentioning
confidence: 99%